Toward data management in university research: the Data asset framework initiative - Torres-Salinas, Daniel (Anuario ThinkEPI, 2010)
Libraries and various agencies are beginning to value research data as an academic product. This situation is bringing out new skills among information professionals, especially in university libraries that are beginning to launch the first proposals, testing methodologies and exploring solutions to begin protecting our users´ research data. We explain one of these initiatives undertaken by the university libraries in the UK, the Data Asset Framework (DAF) initiative. The objective of this project is to identify the characteristics and conditions of the data generated by professors and researchers and use the results to create a framework allowing the implementation of policies for the conservation and preservation of research data.